2022
DOI: 10.1021/acscatal.2c04086
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(II)-Catalyzed Allylic 1,3-Diamination

Abstract: The intermolecular 1,3-diamination reaction of readily available alkenes with N-fluorobis(benzenesulfonamides) catalyzed by rhodium(II) is reported herein. The isomers of the terminal and internal alkenes, even mixtures, all provided the same allylic 1,3-diamine products under mild reaction conditions. The resulting diaminated products can be derived to functionalized diamines and can further generate allylic triamines. Mechanistic studies revealed that the rhodium(II) compounds catalyzed a variety of chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In the course of research, Wang and coworkers also found an interesting one-step route for allylic 1,3-diamination (Scheme 71). 119 The isomers of the alkenes 207 and 208 , one terminal and the other internal, could all be transformed into the same product 209 in 27–88% yields under the conditions of Rh 2 (esp) 2 and NFSI. The reaction mechanism was clarified by radical capture experiments, deuterated reactions and intermediates verification experiments.…”
Section: Dirhodium As a Redox Catalystmentioning
confidence: 99%
“…In the course of research, Wang and coworkers also found an interesting one-step route for allylic 1,3-diamination (Scheme 71). 119 The isomers of the alkenes 207 and 208 , one terminal and the other internal, could all be transformed into the same product 209 in 27–88% yields under the conditions of Rh 2 (esp) 2 and NFSI. The reaction mechanism was clarified by radical capture experiments, deuterated reactions and intermediates verification experiments.…”
Section: Dirhodium As a Redox Catalystmentioning
confidence: 99%
“…Recognizing that the Rh 2 /NFSI catalytic system produces the rhodium metal radical with strong hydrogen abstracting ability, Wang et al [32] . successfully extended this catalytic system to the direct allylic C−H diamination in 2022.…”
Section: Intermolecular 13‐diamination Reactionmentioning
confidence: 99%
“…Recognizing that the Rh 2 /NFSI catalytic system produces the rhodium metal radical with strong hydrogen abstracting ability, Wang et al [32] successfully extended this catalytic system to the direct allylic CÀ H diamination in 2022. Interestingly, despite the structural differences between the terminal alkene 132 and the internal alkene 133, both can produce the same allylic 1,3diamine 134 with this system (Scheme 21a).…”
Section: N-fluorobis(benzenesulfonamide) (Nfsi) As Nitrogenous Reagentsmentioning
confidence: 99%
“…7,8 The short-term nature of these and other renewable energy sources makes energy storage a crucial component of any clean energy infrastructure. [9][10][11][12] Supercapacitors (SCs) are a class of energy storage devices that have received significant interest as promising energy storage frameworks in recent years, due to their rapid charging/ discharging, high working durability, and significant power density (PD). [13][14][15] This makes them promising candidates for applications that would require the supply of high power or rapid harvesting of energy.…”
Section: Introductionmentioning
confidence: 99%